Enhancement of goblet cell hyperplasia and airway hyperresponsiveness by salbutamol in a rat model of atopic asthma. Issue 1 (1st January 2001) - Kamachi, A; Munakata, M; Nasuhara, Y; Nishimura, M; Ohtsuka, Y; Amishima, M; Takahashi, T; Homma, Y; Kawakami, Y
Abstract : BACKGROUND: Goblet cell hyperplasia (GCH) is a prominent feature in animal models of atopic asthma produced by immunisation and following multiple challenges with antigens. The aim of this study was to examine the effect of a β2 agonist on the development of GCH induced by the immune response. METHODS: Brown Norway rats were immunised and challenged with an aerosol of ovalbumin for four weeks. Salbutamol (0.5 mg/kg/day) or vehicle was continuously delivered for the four weeks using a subcutaneously implanted osmotic minipump. The density of goblet cells, other morphological changes, and airway responsiveness to methacholine were evaluated 24 hours after the final challenge. RESULTS: Treatment with salbutamol induced a more than twofold increase in the mean (SE) number of goblet cells (53.7 (7.3) vs 114.5 (11.8) cells/10 3 epithelial cells, p<0.01) while it did not significantly influence airway wall thickening and eosinophilic infiltration. Airway responsiveness to methacholine expressed as the logarithmic value of the concentration of methacholine required to generate a 50% increase in airway pressure (logPC150 Mch) was also enhanced by the β2 agonist (–0.56 (0.21) vs –0.95 (0.05), p<0.05). Additional experiments revealed that the same dose of the β2 agonist alone did not cause GCH in non-immunised rats and that the enhancement of GCH by salbutamol was completely abolished by simultaneous treatment with methylprednisolone (0.5 mg/kg/day). CONCLUSIONS: These data suggest that salbutamol enhances goblet cell hyperplasia and airway hyperresponsiveness in this rat model of atopic asthma.